2011
DOI: 10.1074/jbc.m110.192088
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Modifications of the C-terminal Domain of Tropoelastin Prevent Cell Binding

Abstract: Tropoelastin (TE), the soluble monomer of elastin, is synthesized by elastogenic cells, such as chondrocytes, fibroblasts, and smooth muscle cells (SMCs). The C-terminal domain of TE interacts with cell receptors, and these interactions play critical roles in elastic fiber assembly. We recently found that oxidation of TE prevents elastic fiber assembly. Here, we examined the effects of oxidation of TE on cell interactions. We found that SMCs bind to TE through heparan sulfate (HS), whereas fetal lung fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 57 publications
2
20
1
Order By: Relevance
“…GAG-mediated cell binding has been observed between HDFs and the C-terminal 25 amino acids of bovine tropoelastin. This is in contrast with our current results, as HS does not inhibit HDF attachment to human tropoelastin (12,21). The C termini of human and bovine tropoelastin share a high degree of homology in the domain encoded by exon 36; however, human tropoelastin does not contain domains 34 and 35, which are required in bovine tropoelastin for HS-dependent cell binding.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…GAG-mediated cell binding has been observed between HDFs and the C-terminal 25 amino acids of bovine tropoelastin. This is in contrast with our current results, as HS does not inhibit HDF attachment to human tropoelastin (12,21). The C termini of human and bovine tropoelastin share a high degree of homology in the domain encoded by exon 36; however, human tropoelastin does not contain domains 34 and 35, which are required in bovine tropoelastin for HS-dependent cell binding.…”
Section: Discussioncontrasting
confidence: 57%
“…The overlapping construct containing domains 17-27 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) confirmed that the major cell-binding site in N18 is in domains 17 and 18 of tropoelastin (Fig. 4A).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The Voigt model provided an estimate on the thickness of the adsorbed material on the crystal surface (Voinova et al 1999). Use of a truncated form of tropoelastin devoid of its C-terminal region demonstrated the important role of the C-terminus in binding to HS-perlecan, and identified perlecan as the likely donor of HS chains (Akhtar et al 2011). The protein core of perlecan also mediated interactions with tropoelastin, so it is likely that this region also contributed to the assembly process between these protein moieties.…”
Section: Discussionmentioning
confidence: 97%